A bibliometric analysis of the international medical literature on predatory publishing - Beshyah, Anas; Basher, Momna; Beshyah, Salem (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Introduction: Predatory journals threaten the quality, honesty, and credibility of published scholarly work. This study aimed to provide a quantitative overview of the issues of predatory publishing and journals in international literature. Materials and Methods: We searched the Scopus database for “predatory journalism and publishing” in the abstract, keywords, and title between 2012 and 2018. The Scopus tools were used online for calculations, and VOSviewer was used to construct the visualization maps. Documents were analyzed for bibliographic and citation characteristics such as publication years, languages, countries or regions, journals, articles, and authors. Results: Four hundred and eleven articles were retrieved; 31.3% were “open access;” 46.0% were original research articles. Medical journals were of varying impact. Authors from the USA and affiliated institutions were the most dominant. One author has a clearly evident dedication to the subject being the first to coin the term “predatory” journals. Visualization maps showed sparse associations between most prolific authors, journals, and institutions. Conclusions: This study is the first bibliometric analysis of the threat of predatory journalism to medical research. Increasing anxiety is evident with an uncoordinated strive to fight it. The study represents a starting point to identify and quantify the gaps in the field. It should help pinpoint possible directions and potential collaborations for future action.
Keywords: Bibliometric analysis; citation analysis; health journals; predatory journals; predatory publishing; research ethics